Isolated Infra-Orbital Nerve Schwannoma - Debjyoti Mallick; Saumitra Kumar; Rojan Ravi; Ankita Atin Mukherjee (Bengal Journal of Otolaryngology and Head Neck Surgery, 2024)
Introduction- A schwannoma is a benign tumor that develops from Schwann cells. It’s known to occur more frequently in women than men, and about one third occur in the head & neck area. However, it is rarely associated with the trigeminal nerve, and especially, schwannomas related to the infraorbital nerve are rare.